Propuesta arquitectónica de un centro de desarrollo comunitario con la implementación del bambú para el cantón Quinindé – Esmeraldas - Estupiñán Veliz, Kiana Victoria (2023)
Community development centers promote social integration in communities, becoming a requirement, where participants present their needs through strategies to organize tasks and solve them. This work is carried out through an evaluation of the inhabitants on the architectural proposal of the community development center that will be implemented in the Quinindé canton, province of Esmeraldas. Community development centers promote social integration in communities, becoming a requirement, where participants present their needs through strategies to organize tasks and solve them. This work is carried out through an evaluation of the inhabitants on the architectural proposal of the community development center that will be implemented in the Quinindé canton, province of Esmeraldas.